Contracting-out welfare services : comparing national policy designs for unemployment assistance - O'Sullivan, Siobhan, 1974-; Considine, Mark, 1953- (Broadening perspectives on social policy., 2015)
"Contracting-out Welfare Services: Comparing National Policy Designs for Unemployment Assistance is an edited collection focused on the design and re-design of welfare-to-work systems around the world"--